A Nexus Between Child Labour and Microfinance: An Empirical Investigation1. Issue 1 (6th April 2015) - Chakrabarty, Sayan
Abstract : This research aims to discover whether access to microinsurance might make any difference for the microcredit receivers in reducing child labour by decomposing households into three broad groups: microcredit participants with microinsurance, microcredit participants without microinsurance and non‐participants of microcredit and microinsurance. In extremely poor households, quasi health and/or microlife insurance in combination with microcredit have a significant effect of reducing child labour. In moderately poor households, microinsurance does not make any difference in determining child labour. Microfinance has no role in determining child labour in households above the poverty level.